2010
DOI: 10.4049/jimmunol.1000812
|View full text |Cite
|
Sign up to set email alerts
|

Broad Cross-Reactive TCR Repertoires Recognizing Dissimilar Epstein-Barr and Influenza A Virus Epitopes

Abstract: Memory T cells cross-reactive with epitopes encoded by related or even unrelated viruses may alter the immune response and pathogenesis of infection by a process known as heterologous immunity. Because a challenge virus epitope may react with only a subset of the T cell repertoire in a cross-reactive epitope-specific memory pool, the vigorous cross-reactive response may be narrowly focused, or oligoclonal. We show here, by examining human T cell cross-reactivity between the HLA-A2-restricted influenza A virus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 49 publications
6
80
2
Order By: Relevance
“…Several studies have shown the existence of such heterologous immunity for a variety of viruses, including EBV (53,54). This phenomenon mostly resulted in a skewing of the epitope-specific TCRb repertoire, although a recent study posed the possibility of a diverse heterologous repertoire (55). Finally, disparate nonrestricting MHC alleles have been shown to alter the available repertoire of cognate clonotypes through selective thymic deletion (56).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the existence of such heterologous immunity for a variety of viruses, including EBV (53,54). This phenomenon mostly resulted in a skewing of the epitope-specific TCRb repertoire, although a recent study posed the possibility of a diverse heterologous repertoire (55). Finally, disparate nonrestricting MHC alleles have been shown to alter the available repertoire of cognate clonotypes through selective thymic deletion (56).…”
Section: Discussionmentioning
confidence: 99%
“…There are also preferential expansions of cross-reactive populations of CD8 T cells which can alter the hierarchy of antigen-specific T cell responses, as in lymphocytic choriomeningitis virus-immune mice infected with Pichinde virus, where a subdominant response to the nucleoprotein epitope NP 205-212 becomes dominant (50). In humans it is already wellknown that the IAV M1 58 -66 epitope is highly cross-reactive with other immunodominant HLA-A2-presented epitopes: the EBV BMFL1 epitope from residues 280 to 288 (BMLF1 280 -288 ) and the HIV p17 Gag epitope from residues 77 to 85 (24,40,51). It was previously shown that a substantial part of the acute EBV BMLF1 280 -288 -specific CD8 T cell response during acute infectious mononucleosis (AIM) is mediated by T cells cross-reactive with IAV M1 58 -66 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the highly conserved nature of the M1 protein, clonal senescence may play a role. It is possible that the commonly used VA27-JA42 clonotypes in middle-aged donors may undergo clonal exhaustion or clonal senescence as a result of repeated stimulation of the CD8 T cell response resulting from recurrent seasonal IAV infections or various cross-reactive exposures between different individuals (24,40). On the basis of mouse studies, in some cases the decline in the diversity of the naive TCR repertoire was so extreme that this resulted in holes in the repertoire against usually immunodominant epitopes in aged mice (29).…”
Section: Discussionmentioning
confidence: 99%
“…31 However, during a human study with less similar crossreactive epitopes, Epstein-Barr virus (EBV)-BMLF1 280 and IAV-M1 58 , presumably lower affinity, led to broadening of the crossreactive TCR repertoire during infectious mononucleosis. 59 In general, in vivo studies in mice have shown that an infection with an unrelated virus will induce the formation of new memory cells specific to the second virus and will delete memory cells specific to the previously encountered virus. 35,60 This is a permanent change that remains for the lifetime of the mouse, unless viral antigens remain present or are re-introduced, though this has never been sufficiently studied in humans.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%
“…[57][58][59][60] In a T cell repertoire, that which is common between individuals, be it TCR VA usage or a common amino acid sequence or 'motif', is a public specificity; that which is different between individuals, such as a CDR3 sequence, is a 'private' specificity. Thus, genetically identical hosts have, as a consequence of random DNA recombination events, genetically different immune systems, and this diversity of TCR usage poses a challenge when one considers whether an epitope-specific T cell response may be crossreactive with another epitope.…”
Section: Heterologous Immunity and T Cell Crossreactivitymentioning
confidence: 99%